Sexual dimorphism through androgen signaling; from external genitalia to muscles - Ipulan-Colet, Lerrie Ann (Frontiers in Endocrinology, 2022)
Sexual dimorphisms can be seen in many organisms with some exhibiting subtle differences while some can be very evident. The difference between male and female can be seen on the morphological level such as discrepancies in body mass, presence of body hair in distinct places, or through the presence of specific reproductive structures. It is known that the development of the reproductive structures is governed by hormone signaling, most commonly explained through the actions of androgen signaling. The developmental program of the male and female external genitalia involves a common anlage, the genital tubercle or GT, that later on develop into a penis and clitoris, respectively. Androgen signaling involvement can be seen in the different tissues in the GT that express AR and the different genes that are regulated by androgen in the mesenchyme and endoderm component of the GT. Muscles are also known to be responsive to androgen signaling with male and female muscles exhibiting different capabilities. However, the occurrence of sexual dimorphism in muscle development is unclear. In this minireview, a summary on the role of androgen in the sexually dimorphic development of the genital tubercle was provided. This was used as a framework on analyzing the different mechanism employed by androgen signaling to regulate the sexual dimorphism in muscle development.